Effect of TiO2 on glass structure control of self-crystallized Ba2LaF7 glass-ceramics. Issue 9 (15th June 2020) - Shen, Weihui; Lai, Jun'an; Yang, Yong; Zhou, Dacheng; Qiu, Jianbei; Khan, Muhammad Ibrar; Li, Zhencai; Wang, Qi; Zhang, Ke
Abstract: The structural regulations of Ba2 LaF7 self-crystallized glass-ceramics were successfully analyzed by adjusting the concentration of the doped TiO2 . Increasing the doping concentration of TiO2 tightened the internal structure of the glass and depleted the self-crystallization of Ba2 LaF7 . Further analysis revealed that TiO2 acts as a nucleating agent in the glass-ceramics. However, the number of the crystal nuclei increased, and the growth of the crystal grains was reduced. The change in the internal structure of the glass-ceramics was due to the varying self-crystallization process of Ba2 LaF7 in the glass-ceramics and was not directly caused by the incorporation of TiO2 .